Copper, Cadmium, Chromium and lead bioaccumulation in Stinging Catfish, Heteropneustes fossilis (Bloch) and freshwater mussel, Lamellidens corrianus Lia and to compare their concentration in sediments and water of Turag river (Journal of the Asiatic Society of Bangladesh, Science, 2014)
The present study was carried out to determine the level of bioaccumulation of some heavy metals namely Copper (Cu), Cadmium (Cd), Chromium (Cr) and Lead (Pb) in freshwater fish Stinging catfish (Heteropneustes fossilis Bloch, 1794) and freshwater Mussel (Lamellidens corrianus Lia, 1834) collected from Turag river during the months of October to December 2010. The accumulation levels were then compared with the concentration levels of sediments and water of the same river. In H. fossilis the average bioaccumulations were Cu 13.27 ± 2.47 mg/kg ; Cd 0.215 ± 0.208 mg/kg ; Cr 1.46 ± 0.431 mg/kg and Pb 0 mg/kg in dry weight while Cu 31.90 ± 6.202 mg/kg ; Cd 0.182 ± 0.025 mg/kg ; Cr 0.0367 ± 0.039 mg/kg and Pb 3.865 ± 1.041 mg/kg in dry weight of L. corrianus. Average concentration of metals in sediments of Turag river were Cu 54.95 ± 9.218 mg/kg ; Cd 0.05 ± 0.011 mg/kg ; Cr 5.575 ± 0.608 mg/kg and Pb 34.89 ± 5.554 mg/kg in dry weight and in water these levels were Cu 0.0253 ± 0.024 ppm ; Cd 0.0012 ± 0.001 ppm ; Cr 0.2335 ± 0.044 ppm and Pb 0.1169 ± 0.041 ppm. The bioaccumulation level of heavy metals in Turag river were higher than the FAO approved standard level. DOI: http://dx.doi.org/10.3329/jasbs.v39i2.17862 J. Asiat. Soc. Bangladesh, Sci. 39(2): 231-238, December 2013